2021
DOI: 10.1186/s40479-021-00167-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of dialectical behavior therapy mobile apps for content and usability

Abstract: Background The gap between treatment need and treatment availability is particularly wide for individuals seeking Dialectical Behavior Therapy (DBT), and mobile apps based on DBT may be useful in increasing access to care and augmenting in-person DBT. This review examines DBT based apps, with a specific focus on content quality and usability. Methods All apps referring to DBT were identified in Google Play and iOS app stores and were systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…There are several examples of advanced treatment mental health virtual assistants that recently emerged: Woebot [68], Wysa [69], and Tess [70]. Through brief daily talks and mood monitoring, Woebot offers CBT to clients suffering from sadness and anxiety.…”
Section: Question 3: What Kind Of Therapy Are Used In the Fight Again...mentioning
confidence: 99%
See 3 more Smart Citations
“…There are several examples of advanced treatment mental health virtual assistants that recently emerged: Woebot [68], Wysa [69], and Tess [70]. Through brief daily talks and mood monitoring, Woebot offers CBT to clients suffering from sadness and anxiety.…”
Section: Question 3: What Kind Of Therapy Are Used In the Fight Again...mentioning
confidence: 99%
“…Clustering techniques react to the presence or absence of similarities in each piece of data to identify patterns and assist organize the data. Only two studies [68,69] used clustering to differentiate language usage in online conversations and extract diagnoses from psychiatric reports, respectively. However, data clustering was often used as a first step in classification (as mentioned above) to assist in the selection of features or the identification of labels for the development of supervised learning models [60,71].…”
Section: Question 4: What Types Of Machine Learning Techniques Are Cu...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Linardon et al [ 11 ] found in their meta-analysis that self-guided interventions significantly surpassed waitlist and active controls in efficacy for reducing symptoms of depression and anxiety. Previous studies examining the utility of mental health mobile apps found Wysa to have high usability and engagement ratings [ 12 , 13 ]. In previous studies, general populations and patients [ 14 ] with symptoms of anxiety and depression reported improvements with the use of Wysa.…”
Section: Introductionmentioning
confidence: 99%